2020
DOI: 10.18332/tpc/123822
|View full text |Cite
|
Sign up to set email alerts
|

E-cigarette retailer storefront availability following a nationwide prohibition of e-cigarettes in India: A multicentric compliance assessment

Abstract: INTRODUCTION This study aimed to assess the availability of retailer storefronts that continued to sell electronic nicotine/non-nicotine delivery systems (ENDS/ENNDS) in India, and characterise such retailers following the promulgation of 2019 Indian Ordinance and Act (Ordinance/Act) that prohibit ENDS/ENNDS nationwide. METHODS Discreet observations were conducted of retailer storefronts across different socioeconomic zones in nine major cities of India (Bengaluru, Chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
(51 reference statements)
0
4
0
Order By: Relevance
“…In India, 18.6% of a sample of 199 retailers still sold ENDS following a complete ENDS prohibition [ 60 ]. Most non-compliant retailers were tobacco retailers (94.6%).…”
Section: Resultsmentioning
confidence: 99%
“…In India, 18.6% of a sample of 199 retailers still sold ENDS following a complete ENDS prohibition [ 60 ]. Most non-compliant retailers were tobacco retailers (94.6%).…”
Section: Resultsmentioning
confidence: 99%
“…However, studies have found that they contain chemicals and compounds that can cause equal damage to the health of the person, as with traditional tobacco products [27,28]. Despite a blanket ban on sales of e-cigarettes in India [29], people are still able to access different tobacco products [30], leading to its continued use [31,32]. Thus, availability of a range of tobacco products has led users to experiment various options.…”
Section: Introductionmentioning
confidence: 99%
“…[12] Studies conducted within two-three months of the enactment of PECA 2019 reported, availability of ecigarettes in major Indian cities including Bengaluru, Chandigarh, Dehradun, Delhi, Indore, Kolkata, Ludhiana, Raipur, and Ranchi in 2020 [13]. E-cigarettes were reportedly sold through retail shops [13] underground markets, [14] online. [15,16] In today's world, internet including social media is acting as a powerful conduit for tobacco marketing (including e-cigarettes) and creates a tobacco-permissive context, that is in uential to youth.…”
Section: Introductionmentioning
confidence: 99%
“…The countries with the most restrictive e-cigarette policies (compared to no Regulatory Policies) had 0.6 times lower odds of being current e-cigarette users (aOR 0.6, 95% CI 0.6, 0.7). [12] Studies conducted within two-three months of the enactment of PECA 2019 reported, availability of ecigarettes in major Indian cities including Bengaluru, Chandigarh, Dehradun, Delhi, Indore, Kolkata, Ludhiana, Raipur, and Ranchi in 2020 [13]. E-cigarettes were reportedly sold through retail shops [13] underground markets, [14] online.…”
Section: Introductionmentioning
confidence: 99%